Associations of Illness Perception, Resignation Coping, and Social Support With Self‐Regulatory Fatigue in Patients With Type 2 Diabetes: A Cross‐Sectional Study - Qian Liu; Yijing Zhou; Bing Li; Qiuru Zhuang; Zhier Lin; Zhenrong Zhang; Xiaoying Yan; Kun Zeng; Weiyan Yuan (Nursing Open, 2026)
ABSTRACT Aims To examine the associations among illness perception, resignation coping, social support, and self‐regulatory fatigue (SRF) in patients with Type 2 diabetes mellitus. The study specifically explores whether resignation coping and social support exhibit indirect associations with SRF in the context of illness perception. Design A cross‐sectional study. Methods From November 2024 to October 2025, a convenience sample of 302 adult patients with T2DM was recruited from a tertiary general hospital in China. Participants completed validated instruments with established psychometric properties, namely the Brief Illness Perception Questionnaire, the Medical Coping Modes Questionnaire, the Perceived Social Support Scale, and the Self‐Regulatory Fatigue Scale. Statistical analyses included Spearman correlation and serial mediation analysis using the PROCESS Macro (Model 6) with bias‐corrected bootstrapping. Results SRF was positively correlated with negative illness perception ( r = 0.579, p < 0.01) and resignation coping ( r = 0.612, p < 0.01), and negatively correlated with social support ( r = −0.598, p < 0.01). Serial mediation analysis revealed that illness perception was associated with SRF through indirect pathways involving resignation coping and social support. Resignation coping and social support mediated the association between illness perception and self‐regulatory fatigue, both individually and sequentially. Conclusions Negative illness perception correlates with higher SRF. This observed correlation is additionally linked to indirect pathways involving resignation coping and lower social support. Collectively, these findings highlight a pattern of interrelated cognitive (illness perception), behavioural (resignation coping), and resource (social support) factors that are associated with self‐regulatory fatigue in this cross‐sectional study. Implications for the Profession The findings offer a clear, evidence‐based framework for nursing practice. They highlight the potential value of integrated assessment and intervention that simultaneously addresses patients' illness beliefs, maladaptive coping strategies, and social support systems, which are associated with lower SRF and better diabetes self‐management. Reporting Method This study adheres to the Strengthening the Reporting of Observational Studies in Epidemiology (STROBE) guidelines for cross‐sectional studies. Patient or Public Contribution Patients participated solely as research participants by providing survey data. They were not involved in the study design, implementation, data analysis, interpretation, or manuscript preparation. All patients provided written informed consent prior to questionnaire completion.